Nunggak semi Al Suwardi: organology and perspective of harmonic planet music creation - Aton Rustandi Mulyana; Joko Suranto (International Journal of Visual and Performing Arts, 2021)
This article examines the artistry of a composer named Aloysius Suwardi. This composer, who grew up in the Javanese gamelan music tradition, has produced musical compositions and created musical instruments as a means/medium to express it on the journey of his creativity. His works have been staged in various forums or world music festivals. The musical instruments he has created fill the laboratory spaces to create his musical compositions. Two musical ensembles that have been created are Gamelan Genta and Gamelan Planet Harmonic. These two musical instruments complement the many personal musical instruments he has created, such as the vibrander, tering, gerendang, and other musical instruments. Regarding the two ensembles, this article examines the aspects of the creation process. For example, how did Al Suwardi choose the materials used, how to make them, to how he determined the barrel system for these tools. In terms of compositing, this article examines how Al Suwardi started his work, his models of creation, and how he composes his works until they are declared final. The gragas and dridis creeds and Nunggak Semi's concept are the main topics in this composition creation model. Both creeds and concepts have ushered in the landscape of making Al Suwardi's musical compositions expand, from the gamelan tradition to more contemporary models of music creation